PENGARUH FINANCIAL LITERACY TERHADAP BUSINESS SUSTAINABILITY PADA UMKM DESA PANGGUNGHARJO - Lilik Ambarwati; Lukia Zuraida (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
The SMEs sector is one of the drivers of the economy, but in its development there are still many unresolved problems, one related to finance. The purpose of this research is to know the influence of financial literacy or financial knoledge owned by the SMEs businessman (manager) toward the sustainability of their business from the SMEs in the village of Panggungharjo. This research is a quantitative research, using simple linier regression to test the hypothesis and take the population is SMEs in the village of Panggungharjo, while the data is obtained through questionnaires to 30 SMEs in the village of Panngungharjo. Independent variables in this research are financial literacy and business sustainability is dependent variable. The result showed that financial literacy gives effect to business sustainability of 33.8%. It shows that financial literacy or financial knowledge owned by the SMEs businessman (manager) in Panggungharjo is important in supporting the sustainability of their business.